2021
DOI: 10.1001/jamaophthalmol.2021.3477
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ocular Adverse Events With Inactivated COVID-19 Vaccination in Patients in Abu Dhabi

Abstract: s of March 2021, the COVID-19 pandemic has caused 35 million infections and more than 1 million deaths worldwide, leading to the urgent demand for a vaccine. 1 To date, 2 inactivated vaccine candidates have been reported to protect against SARS-CoV-2. The inactivated COVID-19 vaccine by Sinopharm's China National Biotec Group is mixed with aluminum-based adjuvant and has been found tolerable and immunogenic in healthy people with 2 doses administered 21 days apart. 2 As of March 2021, the United Arab Emirates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
142
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(147 citation statements)
references
References 15 publications
4
142
0
1
Order By: Relevance
“…Rabinovitch et al reported twenty one cases of uveitis after COVID-19 vaccination in Israel, of which nineteen were diagnosed with anterior uveitis and two developed multiple evanescent white dot syndrome (MEWDS) [ 24 ]. Recently, Pichi et al described seven patients diagnosed with episcleritis (1), anterior scleritis (2), acute macular neuroretinopathy (AMN) (2), paracentral acute middle maculopathy (PAMM) (1), and subretinal fluid (1) after COVID-19 vaccination [ 25 ]. None of these studies was a multicentral case series.…”
Section: Discussionmentioning
confidence: 99%
“…Rabinovitch et al reported twenty one cases of uveitis after COVID-19 vaccination in Israel, of which nineteen were diagnosed with anterior uveitis and two developed multiple evanescent white dot syndrome (MEWDS) [ 24 ]. Recently, Pichi et al described seven patients diagnosed with episcleritis (1), anterior scleritis (2), acute macular neuroretinopathy (AMN) (2), paracentral acute middle maculopathy (PAMM) (1), and subretinal fluid (1) after COVID-19 vaccination [ 25 ]. None of these studies was a multicentral case series.…”
Section: Discussionmentioning
confidence: 99%
“…5 Adverse ocular sequelae of the pandemic have also been linked to treatment protocols, 6 positioning during intensive care unit stay, 7 lockdown restrictions, 8 and immunization. 9 Mucormycosis is a life-threatening, opportunistic, angioinvasive fungal infection that occurs in immunocompromised individuals, especially those with uncontrolled diabetes mellitus (DM). 10 The disease often starts in the paranasal sinuses with spread to the surrounding tissues, including the orbit.…”
Section: Introductionmentioning
confidence: 99%
“…The subjects’ symptomatic decrease in visual acuity resolved after receiving topical corticosteroids and additional oral NSAIDs in one subject. Pichi et al reported two cases of anterior scleritis after receiving the BBIBP-CorV vaccine [ 51 ]. One patient presented with pain and redness in both eyes 1 week after receiving a dose of the vaccine, which resolved after a tapering dose of topical steroids.…”
Section: Covid-19 Vaccine-associated Ocular Inflammationmentioning
confidence: 99%
“…Pichi et al reported a case of episcleritis in a patient who had previously received the BBIBP-CorV vaccine. However, further details of the case were not reported [ 51 ].…”
Section: Covid-19 Vaccine-associated Ocular Inflammationmentioning
confidence: 99%
See 1 more Smart Citation